Enhancing Pre Reading Interest Through The Smart Floor Educational Play Tool In Early Childhood Education - Alya Noerohmah; Eva Manfaatin Kartadinata; Ika Rustika Zainah (FKIP UNSULTRA, 2026)
Early reading interest in young children often decreases when literacy activities rely on teacher-centered instruction and repetitive worksheets. This study aimed to improve the pre-reading interest and skills of children aged 5–6 years through the use of the Smart Floor educational play tool. The study addresses the need for innovative, play-based literacy instruction that is developmentally appropriate and actively engages young children in early reading experiences. The study used classroom action research with two cycles, consisting of planning, action, observation, and reflection. The participants were 23 children in Group B.1 at PAUD Baitul ‘Ulum Cianjur. Data were collected through observation, interviews, checklists, and documentation, then analyzed using descriptive qualitative analysis and percentage calculation. The findings showed a gradual improvement in children’s pre-reading achievement. The average pre-reading score increased from 56% in the pre-cycle to 73% in Cycle I and reached 85% in Cycle II, exceeding the predetermined success criterion. Children became more active, focused, confident, and enthusiastic in recognizing uppercase letters, lowercase letters, letter sounds, letter forms, and simple words. The most notable improvement occurred in phonics recognition, which increased from 52% to 90%, indicating substantial progress in children's ability to associate letters with their corresponding sounds. The study concludes that Smart Floor can create an active, enjoyable, and meaningful literacy environment. This media supports children’s early literacy development through movement, symbols, sound recognition, and direct interaction. The novelty of this study lies in integrating movement-based educational play with structured pre-reading instruction through a cyclical classroom action research approach. The findings contribute to the growing body of literature on play-based literacy learning and provide practical guidance for teachers seeking child-centered strategies to support early literacy development in early childhood education settings.